Periprocedural Considerations for Patients with Gastric Electrical Stimulators. Issue 6 (29th July 2019) - Nadherny, Weston Case; Anderson, Brooke; Abd‐Elsayed, Alaa
Abstract : Objectives: Gastric electrical stimulation (GES) is a technology that uses neurostimulation for the modulation of gastric activity. In clinical practice, the most commonly encountered form of GES is high frequency GES. GES devices are typically used for the treatment of refractory gastroparesis, although they have also been investigated for obesity management and the treatment of refractory gastroesophageal reflux disease. Just as many patients with chronic diseases require surgery, patients with an implanted GES device may encounter the need for periprocedural care. Therefore, the purpose of this review is to address the special needs of patients with an implanted GES device. Materials and methods: A systematic computerized search of the literature was performed to consolidate existing knowledge on GES management in the periprocedural setting. Duplicate results were eliminated, and results were further narrowed based on title and abstract. All articles with possible relevance were then reviewed in full. Manufacturer information including pamphlets and websites were also reviewed. Results: A total of 1201 articles were identified for initial review, and 33 met inclusion criteria. Conclusions: Available data suggests GES is a technology with increasing prevalence. When patients with an implanted GES device present for periprocedural care, the anesthesia staff must consider the device when planning for the procedure. Topics addressed include general anesthetic considerations, nerve localization, radiation exposure, electrocautery, diathermy, emergency external defibrillation, and MRI compatibility.